The Role of Digital Nomad Communities in Fostering Peaceful Cross-Cultural Exchange and Economic Growth in West Africa - Bello, Mukhtar (Kashere Journal of Politics and International Relations, 2025)
The Digital nomadism is a lifestyle leveraging technology for remote work and global mobility, is gaining traction in West Africa, a region rich in cultural diversity and emerging digital economies. This study examines how digital nomad communities in Lagos, Accra, and Dakar contribute to peaceful cross-cultural exchange and economic growth. Using a mixed-methods approach, including surveys of 150 nomads, interviews with 50 stakeholders, and economic data analysis, the research reveals that nomads foster cultural understanding through collaborative initiatives like workshops and festivals, with 70% of nomads and 60% of locals reporting reduced stereotypes (study data, 2025). Economically, nomads drive growth, contributing 2% to Lagos’s GDP through $1,200 monthly spending and generating 200 jobs in Accra via mentorships (study data, 2025). However, challenges such as gentrification, with 22% rent increases in Lagos, and infrastructure gaps, like unreliable electricity, pose risks. These findings suggest that digital nomadism can enhance West Africa’s global economic role if supported by policies like digital nomad visas and infrastructure investments. For policymakers, the study advocates equitable frameworks to balance economic benefits with local needs. Local communities can leverage nomad collaborations for cultural and economic gains, while global stakeholders should recognize West Africa’s potential as a nomad hub, fostering sustainable development through inclusive integration.